Therapeutic monitoring of psychoactive drugs - antidepressants: a review - Grundmann, Milan; Kacirova, Ivana; Urinovska, Romana (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2015)
BACKGROUND: Major depression, is one of the most prevalent mental disorders in Europe and the USA. The dramatic rise in pharmacological antidepressants is mainly due to increase in use of selective serotonin reuptake inhibitors, serotonin and norepinephrine reuptake inhibitors and other new generation antidepressants. In clinical practice, optimum individual doses are often guided by trial-and-error. This article reviews the available literature on therapeutic monitoring of antidepressant drugs. METHODS: A search using MEDLINE (english-language reports, 1983 - August 2012) with the key words for antidepressant drugs and therapeutic drug monitoring. RESULTS: There is a need for monitoring antidepressants due to wide interindividual pharmacokinetic variability. At the same drug dose, a more than 20-fold variation in steady state concentration of drug in the body may result: people differ in their ability to absorb, distribute, metabolise and excrete drugs for reasons of concurrent disease, age, gender, smoking and eating habits, concomitant medication and genetics. CONCLUSIONS: Monitoring of antidepressant drugs enables us to individualise drug doses based on rational therapy, minimalise side effects, reduce morbidity and mortality and cut the cost of health care. Phenotyping and genotyping could increase therapeutic drug monitoring furthere.
Keywords: depresivní porucha unipolární; antidepresiva; Depressive Disorder, Major; psychotropní léky; Drug Monitoring; lidé; Antidepressive Agents; Psychotropic Drugs; Humans; monitorování léčiv